2007
DOI: 10.1542/peds.2005-2969
|View full text |Cite
|
Sign up to set email alerts
|

XXY (Klinefelter Syndrome): A Pediatric Quantitative Brain Magnetic Resonance Imaging Case-Control Study

Abstract: OBJECTIVE. An extra X chromosome in males (XXY), known as Klinefelter syndrome, is associated with characteristic physical, cognitive, and behavioral features of variable severity. The objective of this study was to examine possible neuroanatomical substrates of these cognitive and behavioral features during childhood and adolescence. METHODS. MRI brain scans were acquired for 42 XXY and 87 healthy XY age-matched control males. We compared these 2 groups on regional brain volumes and cortical th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
136
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(149 citation statements)
references
References 41 publications
11
136
1
1
Order By: Relevance
“…Previous studies have separately examined regional volume differences in TS and KS (Patwardhan et al, 2000;Kesler et al, 2004;Molko et al, 2004;Giedd et al, 2007), including earlier independent findings on these cohorts from our group (Bryant et al, 2011;Marzelli et al, 2011). Not surprisingly, our findings are highly consistent with these studies and provide further evidence for neuroanatomical correlates of an X-chromosome gene dosage effect.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have separately examined regional volume differences in TS and KS (Patwardhan et al, 2000;Kesler et al, 2004;Molko et al, 2004;Giedd et al, 2007), including earlier independent findings on these cohorts from our group (Bryant et al, 2011;Marzelli et al, 2011). Not surprisingly, our findings are highly consistent with these studies and provide further evidence for neuroanatomical correlates of an X-chromosome gene dosage effect.…”
Section: Discussionsupporting
confidence: 89%
“…The volume of specific cerebral regions involved in different abilities (language, verbal memory, executive function, and social processes) was also studied. A lower volume of the gray matter of the frontal and temporal lobe, as well as of cerebellar hemispheres, was reported in comparison to cytogenetically normal males [DeLisi et al, 2005;Giedd et al, 2007]. Reduced amygdala, hippocampal, superior temporal gyrus and caudate volumes were also reported by some authors [Patwardhan et al, 2000;Itti et al, 2006].…”
Section: The Cognitive Phenotypementioning
confidence: 74%
“…The neural mechanisms underlying the cognitive/behavioral phenotype of Klinefelter patients have been studied by several authors with both structural and neuroimaging methods. A reduced total brain volume in Klinefelter patients has been reported by several authors using magnetic resonance imaging (MRI) [Shen et al, 2004;DeLisi et al, 2005;Giedd et al, 2007], even though this finding was not confirmed by other authors [Patwardhan et al, 2000[Patwardhan et al, , 2002Rose et al, 2004]. The volume of specific cerebral regions involved in different abilities (language, verbal memory, executive function, and social processes) was also studied.…”
Section: The Cognitive Phenotypementioning
confidence: 93%
“…Understanding the relative contributions of sex chromosomes and hormones may provide clues as to the mechanisms of development in health and illness (Clark et al, 1988;Diener et al, 1985;Morse et al, 1986). Toward this goal our group is studying subjects with anomalous sex chromosome variations (eg, XXY, XXX, XXXY, XYY) (Giedd et al, 2007), as well as subjects with anomalous hormone levels (eg, congenital adrenal hyperplasia, familial male precocious puberty, and Cushing syndrome) (Merke et al, 2003;Merke et al, 2005).…”
Section: Mapping-mechanismsmentioning
confidence: 99%